A brief overview about the adipokine: Isthmin-1 - Hu, Min; Zhang, Xin; Hu, Can; Teng, Teng; Tang, Qi-Zhu (Frontiers in Cardiovascular Medicine, 2022)
Isthmin-1 is a secreted protein with multiple capability; however, it truly attracts our attention since the definition as an adipokine in 2021, which exerts indispensable roles in various pathophysiological processes through the endocrine or autocrine manners. In this review, we summarize recent knowledge of isthmin-1, including its distribution, structure, receptor and potential function.